2006
DOI: 10.1210/jc.2005-1475
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Level of Visfatin/Pre-B Cell Colony-Enhancing Factor in Patients with Type 2 Diabetes Mellitus

Abstract: Our results indicate that visfatin may play a role in the pathogenesis of T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
469
13
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 596 publications
(543 citation statements)
references
References 34 publications
44
469
13
17
Order By: Relevance
“…Thus, in addition to its relationship with visceral fat, visfatin quantification may also serve as a marker of glucose homeostasis. This is supported by reports demonstrating that visfatin expression and release is increased in obese subjects and in patients with type 2 diabetes mellitus [7,8] where plasma concentrations are substantially higher than in healthy young subjects. Plasma visfatin concentrations using this assay are generally <1.0 ng/ml in healthy young subjects.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, in addition to its relationship with visceral fat, visfatin quantification may also serve as a marker of glucose homeostasis. This is supported by reports demonstrating that visfatin expression and release is increased in obese subjects and in patients with type 2 diabetes mellitus [7,8] where plasma concentrations are substantially higher than in healthy young subjects. Plasma visfatin concentrations using this assay are generally <1.0 ng/ml in healthy young subjects.…”
Section: Discussionsupporting
confidence: 68%
“…Circulating visfatin concentrations were found to be correlated with the amount of visceral fat in healthy non-obese humans [6], consistent with the finding that increased visfatin release and expression is associated with obesity and diabetes in this tissue [7,8]. Further, increased plasma visfatin concentrations were reduced after weight loss in morbidly obese subjects [9].…”
supporting
confidence: 77%
“…In humans, the normal fasting PBEF level is 10-40 ng/ml [1][2][3][4][5], which equals 180-700 pmol/l for this 55 kDa protein, 3.6-14 times the concentration of the normal fasting insulin level (50 pmol/l). If PBEF could act with the same efficacy as insulin [1], it should contribute importantly to the regulation of glucose metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…Visfatin was also shown to mimic the effect of insulin with the same efficacy in rodent cells in vitro and in mouse models [1]. However, subsequent studies in human subjects reported conflicting results with regard to its relation with adiposity [2][3][4], subcutaneous or visceral fat [2,3], and insulin resistance [3][4][5], suggesting that the role of this protein in the development of obesity and insulin resistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation